An economic feasibility study for the production of apple cider vinegar in Lattakia Governorate – Syria - Fadel, Nour Ahmad; Saker, Ibrahim Hamdan (Journal of agricultural, environmental and veterinary sciences, 2021)
The presence of an excess of the apple crop, and the increasing problem of its marketing in case the season is exposed to bad weather conditions, makes the best solution to confront this problem by manufacturing apple cider vinegar, as the apple cider vinegar manufacturing project emerges as an important model for the application of small agricultural projects in Syria, during the next stage, so the aim of the research To study the economic feasibility of a project to manufacture apple cider vinegar in apple- growing areas within Lattakia Governorate in Syria. To achieve the objectives of the research, the descriptive approach and the case study approach were used to study the hypotheses of the study, the most important of which is the existence of an economic feasibility for the manufacture of apple cider vinegar, or the lack of feasibility. The investor is 47.53%, based on production costs, 115.03%, while the profitability coefficient based on the invested capital is 44.49%, and for production costs, 107.67%, and the recovery time of the invested capital is 1.37 years. That is, this project, which achieves an added value, especially for apples that are not suitable for marketing, concludes the research with a number of recommendations, the most important of which is that it should work to encourage agricultural investors to enter this field by providing loans through village banks, development or small projects, and securing a market exchange. for their products, and opening new markets, especially in the field of export.